Risk factors for acute hepatitis B and its progression to chronic hepatitis in Shanghai, China. Issue 12 (28th August 2008) - Zhang, H W; Yin, J H; Li, Y T; Li, C Z; Ren, H; Gu, C Y; Wu, H Y; Liang, X S; Zhang, P; Zhao, J F; Tan, X J; Lu, W; et al.
Abstract : Background and aims: The major risk factors for acute hepatitis B (AHB) in China and the viral factors determining the progression from acute to chronic hepatitis B remain largely unknown. Methods: Epidemiological studies within a population-based surveillance for AHB in adults were performed in Shanghai, China, including 294 patients, 588 matched controls and 572 family members of the patients. Results: Invasive medical procedures, household contact with hepatitis B virus (HBV) carriers, body care and beauty treatments, and lack of HBV vaccination were independently associated with AHB. Among those risks, pedicure in bath centres emerged. Sixty-eight of 128 patients with AHB were genotyped including 33 with HBV B2 and 35 with HBV C2. Twenty-five (8.50%) of the 294 patients, including 20 with HBV C2 and 5 with HBV B2 (p = 0.013), progressed to chronic infection. Multivariate analysis showed that HBV C2 was independently associated with chronicification of AHB. Patients with HBV B2 were younger and there was a higher proportion of women than those with HBV C2. The prevalence of HBV B2 was higher in the patients than in neighbourhood chronic carriers. The chronic carriers with HBV B2 showed higher viral loads, higher hepatitis B e antigen (HBeAg) seropositivity, and with higher proportion in men than those with HBV C2, implying that sexual contact plays a role in the transmission of HBV B2. Phylogenetic analysis showed that HBV C2 was frequently involved in transmissions within households. Conclusions: Despite lower viral load and HBeAg status in the chronic carriers, HBV C2 was more prone to causing chronic infection than was HBV B2.